(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Impact of gestational diabetes mellitus (GDM) on the coagulation system still remains unclear and there is limited data available regarding haemostatic changes in GDM in Bangladesh. This study was aimed at determining plasmaprothrombin time (PT), activated partial thromboplastin time (APTT) in women with GDM. This cross sectional study encompassed 44 GDM (age: 28.5±3.8 years, BMI: 27.2±4.0kg/m2; mean±SD) and equal number of pregnant women with normal glucose tolerance (NGT) diagnosed on the basis of WHO criterion 2013 at or after 24 weeks of gestation to see PT and APTT. Plasma glucose was measured by glucose oxidase method, PT and APTT by automated coagulation analyzer. There was no statistically significant difference between the GDM and NGT groups for PT (12.3±0.5 vs. 12.2±0.4 sec, mean±SD; P=0.40) or APTT (30.53±1.01 vs. 30.9±4.5 sec, mean±SD; P=0.56). In conclusion, PT and APTT do not differ between women with or without GDM. BSMMU J 2022; 15(3): 146-150